New World Irish - Morgan, J. author. aut Link
XX, 276 p.
Keywords: The book concerns the new World Irish, tracing the developing profile of the Irish in America from the Famine forward. The studies draw their material from roughly a one-hundred-year arc of Irish presence and relevance in American life and they would serve as American as well as Irish-American studies.